2017
DOI: 10.1038/s41598-017-12477-2
|View full text |Cite
|
Sign up to set email alerts
|

Host genetic background influences diverse neurological responses to viral infection in mice

Abstract: Infection by Theiler’s murine encephalomyelitis virus (TMEV) is a model for neurological outcomes caused by virus infection because it leads to diverse neurological conditions in mice, depending on the strain infected. To extend knowledge on the heterogeneous neurological outcomes caused by TMEV and identify new models of human neurological diseases associated with antecedent infections, we analyzed the phenotypic consequences of TMEV infection in the Collaborative Cross (CC) mouse population. We evaluated 5 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 124 publications
2
27
0
Order By: Relevance
“…The current data are the first to provide evidence that indicates genetic deletion of Ido1 increases the incidence of seizures during acute TMEV infection of C57BL/6J mice. Genetic background is known to play a role in the pathogenesis of TMEV‐induced neurological diseases, which has been recently exemplified through the use of the Collaborative Cross mouse population . Importantly, all mice used in this study were on the C57BL/6J background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current data are the first to provide evidence that indicates genetic deletion of Ido1 increases the incidence of seizures during acute TMEV infection of C57BL/6J mice. Genetic background is known to play a role in the pathogenesis of TMEV‐induced neurological diseases, which has been recently exemplified through the use of the Collaborative Cross mouse population . Importantly, all mice used in this study were on the C57BL/6J background.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic background is known to play a role in the pathogenesis of TMEV-induced neurological diseases, which has been recently exemplified through the use of the Collaborative Cross mouse population. 20 Importantly, all mice used in this study were on the C57BL/6J background. Although it is beyond the scope of the current study, given the seemingly protective role of Ido1 in mitigating the occurrence of TMEV-induced seizures during acute infection, it would be interesting to compare the expression of this gene in mouse strains that are resistant to seizures (ie, SJL).…”
Section: Discussionmentioning
confidence: 99%
“…The CC strains are derived from 8 founder mouse strains that include 5 classic inbred strains and 3 wild-derived strains [1][2][3][4]. We and others have previously shown that the CC can be used to model the diversity in human immune responses and reproduce human disease states not captured in standard inbred mouse models [5][6][7][8][9][10][11][12][13][14], and we additionally demonstrated that the CC better represents the large diversity in T-cell immunophenotypes represented in the human population [15]. Thus, the CC affords us with the ability to study immunity and clinical disease to infection in an animal model with diverse genotypes.…”
mentioning
confidence: 99%
“…Highlighting another powerful characteristic of the CC, completely new mouse models for spontaneous colitis [41], Ebola-associated hemorrhagic fever [42], novel neurological responses to Theiler's murine encephalomyelitis virus (TMEV) [43], and persistent West Nile virus (WNV) infection in the brain [44] were discovered, a harbinger of new model systems that may emerge over time.…”
Section: The Collaborative Crossmentioning
confidence: 99%